Subchondral insufficiency fracture of the knee: progress in the pathogenesis and treatment - Wang, Ziyue; Zhang, Yi; Yuan, Jiale; Wang, Chao; He, Bangjian; Pei, Hang (Frontiers in Surgery, 2025)
Subchondral Insufficiency Fracture of the Knee (SIFK) is a disease with unclear pathogenesis and rapid progression, it is prone to developing end-stage osteoarthritis. Due to the lack of a definitive treatment strategy for SIFK in the clinic, knee replacement is often the preferred measure. However, in recent years, as the disease has become better understood, more and more effective treatments have been proposed, but there is a lack of summarization. Therefore, this article summarizes its pathogenesis and therapeutic advances.